Subacute Spinal Subdural Hematoma in One-Year Old Boy Due to Severe Hemophilia A - Tun Paksi Sareharto; Suciati Jandraningrum; Vetty Kurniawati; Agus Priambodo; Alifiani Hikmah Putranti (Faculty of Medicine, Diponegoro University, 2021)
Background: Paraparesis may result from a variety of or primary central nervous system conditions or systemic disorders, and although rare, it may also caused by spinal cord hemorrhage. Spontaneous spinal subdural hematomas (SSDH) are most frequently associated with coagulopathies. People with congenital clotting disorders such as hemophilia are at increased risk for experiencing spontaneous spinal subdural hemorrhage at unusual sites, which is a rare case and a neurological emergency required urgent recognition. We report a boy with paraparesis caused by subacute SSDH due to hemophilia A. Case Presentation: A 15 month-old boy, with chief complain of difficulty in moving his leg and pain when walking, physical examination revealed a lower motor neuron lesion, laboratory showed a low factor VIII at 0.4% level, Magnetic Resonance Imaging (MRI) showed anterior and posterior displacement of the spinal cord due to the presence of the subacute subdural hematoma extending from 1st cervical to 1st lumbar spine. He assessed with inferior paraparesis caused by subacute spinal subdural hematoma due to hemophilia A. The patient’s condition was improved after received replacement therapy of factor VIII and proper laminectomy neurosurgery. Conclusion: This case showed an approach for a comprehensive diagnostic and management for a rare case of paraparesis due to hemophilia. Pay attention to the physical examination which shows a lower motor neuron lesion in an acute paralysis cases, there is still a possibility that it is an upper motor neuron lesion.